2020
DOI: 10.7554/elife.58613
|View full text |Cite
|
Sign up to set email alerts
|

Modular output circuits of the fastigial nucleus for diverse motor and nonmotor functions of the cerebellar vermis

Abstract: The cerebellar vermis, long associated with axial motor control, has been implicated in a surprising range of neuropsychiatric disorders and cognitive and affective functions. Remarkably little is known, however, about the specific cell types and neural circuits responsible for these diverse functions. Here, using single-cell gene expression profiling and anatomical circuit analyses of vermis output neurons in the mouse fastigial (medial cerebellar) nucleus, we identify five major classes of glutamater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
297
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(327 citation statements)
references
References 242 publications
(348 reference statements)
29
297
1
Order By: Relevance
“…The FN projects to a myriad of downstream targets that play various roles in both motor and nonmotor functions [36][37][38][39][40][41] . In this study, we mainly focused on the FN-MdV pathway, yet it is possible that MdV-projecting FN neurons provide efference copies to many other brain regions by their collateral projections 76 . We observed that inhibiting FN output could directly affect task-related IN activity.…”
Section: Discussionmentioning
confidence: 99%
“…The FN projects to a myriad of downstream targets that play various roles in both motor and nonmotor functions [36][37][38][39][40][41] . In this study, we mainly focused on the FN-MdV pathway, yet it is possible that MdV-projecting FN neurons provide efference copies to many other brain regions by their collateral projections 76 . We observed that inhibiting FN output could directly affect task-related IN activity.…”
Section: Discussionmentioning
confidence: 99%
“…It forms crucial connections with motor and non-motor systems, thus being implicated in various emotional activities and contributing to a coordinated response to internal and external stimuli [ 78 ]. The fastigial glutamatergic projection neurons can modulate the cortical circuits by crossing midline and synapsing with the midbrain and thalamus [ 79 ]. Disruptions of the cerebello-thalamo-cortical circuits seem to occur in several psychiatric disorders.…”
Section: Mediodorsal Thalamic Relationship With the Cerebellummentioning
confidence: 99%
“…The cerebellar vermis, which is most consistently associated with emotional pathologies and fear expression 20,24,30 , but see ref. 31 , projects to the fastigial nucleus (FN), one of the deep cerebellar nuclei that projects to many targets from the spinal cord to the diencephalon 22,32 . The purpose of the present work is to study the contribution of specific FN output pathways to fear learning.…”
mentioning
confidence: 99%